Najah Al-Qari Sharh Sahih Al-Bukhari by Youssef Effendi Zadeh (1167 AH) from the Topic of Surrendering a Few people over a Lot, to the chapter on the Disclosure of Peace (study and investigation) - Hussain, Hussein; Abd , Khamis (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to God, Lord of the worlds, and prayers and peace be upon our Prophet and his good family and companions. As for after: They begin to work, read, and detail, which is the outline of the Noble Qur’an, and its principle and detailed for its year, and I have taken care of this ummah by the Chosen One’s hadith - - careful attention to memorization, writing, explanation and deduction, thanks to those whom God Almighty has appointed for this matter, so he rewarded them with Islam and its people. It is known that the two Sahihs are greatest books of Islamic legislation, after the Holy Qur’an, and the specialists have intended them to narrate, explain and explain their chain of narrators and their contents, including Sheikh Yusuf Zadeh in his commentary Najah al-Qari’s explanation of Sahih al-Bukhari, and the last of our claim is that praise be to God, Lord of the worlds, and prayers and peace be upon the master Messengers and his good and pure family and companions, and those who followed them with kindness until the Day of Judgment.